IMPLEMENTASI MANAJEMEN PENDIDIKAN INKLUSI UNTUK ANAK BERKEBUTUHAN KHUSUS DI SD IT ANNIDA SOKARAJA - Cholish, Cholish Nur Fauzi; Hanif, Muhammad Hanif (JPI (Jurnal Pendidikan Inklusi), 2025)
This study aims to describe the implementation of the inclusive education program at SD IT Annida Sokaraja through the stages of preparation, organization, implementation, supervision, and identifying things about the advantages and disadvantages as a form of support and obstacles in its implementation. This study uses a qualitative approach with several methods used, namely data collection techniques in the form of observation, interviews, and documentation. The subjects of this study were all components involved in the implementation of inclusive education at SD IT Annida Sokaraja, namely the Principal, Deputy Curriculum, Inclusion Coordinator and Special Guidance Teacher. The results of this study indicate that planning is carried out by identifying children who are classified as children with special needs and preparing special guidance teachers. In the organizing stage, guidance teachers are distributed according to the category and needs of the child. The implementation of learning is carried out conditionally, adjusting to the characteristics of individual children. Evaluation of student achievement and development is carried out periodically through daily report books and Individualized Education Programs (IEP) which are discussed with parents. Supporting factors in the implementation of the inclusion program include the availability of special guidance teachers and a form of appreciation from the Social Service. Meanwhile, the obstacles faced include the lack of understanding and competence of teachers in dealing with the emotional conditions of ABK. This finding emphasizes the importance of strengthening teacher capacity and a collaborative evaluation system in realizing inclusive and equitable education.